2018
DOI: 10.21849/cacd.2018.00409
|View full text |Cite
|
Sign up to set email alerts
|

Clinician Survey on Speech Pathology Services for People with Aphasia in Hong Kong

Abstract: This study aims to investigate aphasia practices by speech-language pathologists working with clients suffering from acquired neurogenic communication disorders through an online survey. Questions pertaining to content and intensity of aphasia management, service adequacy, and barriers to effective service provision to persons with aphasia were asked to understand the current service-provision situation in Hong Kong. A web-based questionnaire containing 38 questions was electronically distributed to speech-lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 30 publications
(10 reference statements)
2
18
0
Order By: Relevance
“…Australian therapists reported that a functional approach was most widely used in aphasia therapy (M. Rose et al, 2014;Verna et al, 2009). This has also been reported in international research (Guo et al, 2014;Kong & Tse, 2018). Functional approaches seek to reduce the activity limitation and participation restriction associated with aphasia and have a focus on enhancing communicative ability in everyday life (Patterson & Chapey, 2008).…”
Section: Usual Care In Aphasia Therapymentioning
confidence: 91%
See 1 more Smart Citation
“…Australian therapists reported that a functional approach was most widely used in aphasia therapy (M. Rose et al, 2014;Verna et al, 2009). This has also been reported in international research (Guo et al, 2014;Kong & Tse, 2018). Functional approaches seek to reduce the activity limitation and participation restriction associated with aphasia and have a focus on enhancing communicative ability in everyday life (Patterson & Chapey, 2008).…”
Section: Usual Care In Aphasia Therapymentioning
confidence: 91%
“…When describing usual care therapy, many elements have been considered such as the amount and frequency of therapy provided (Verna et al, 2009), the theoretical approach or nature of the treatment sessions (Guo et al, 2014;Kong & Tse, 2018;Verna et al, 2009), and the way in which outcomes are measured (Verna et al, 2009). These descriptions of usual care constitute a broad look at usual care therapy and aimed to reflect current practice and therapists' clinical decision-making with data collected through surveys reflecting clinicians' perspectives of therapy provided.…”
Section: Introductionmentioning
confidence: 99%
“…This evidence gap is compounded by an evidence‐practice gap including the provision of aphasia‐friendly information, support with depression and SLT of adequate intensity to maximise effectiveness (Code & Petheram, 2011; Foster, Worrall, Rose, & O'Halloran, 2015; Hickey, Shrubsole, Worrall, & Power, 2019; Hilari et al., 2015; Rose, Worrall, McKenna, Hickson, & Hoffmann, 2009; Shrubsole, Worrall, & Power, 2019; Shrubsole, Worrall, Power, & O'Connor, 2018; Thomas et al., 2013; Trebilcock et al., 2019). Surveys of SLTs in Australia and Hong Kong highlighted that PWA received sub‐optimum dosage for effective therapy (Kong, 2011; Kong & Tse, 2018; Rose, Ferguson, Power, Togher, & Worrall, 2014; Verna, Davidson, & Rose, 2009). This echoes earlier surveys in Australia, Canada, the United Kingdom and the United States (Katz et al., 2000; Mackenzie et al., 1993; Verna et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…They noted that access to SLT was variable (a ‘post‐code lottery’), with better access in the first year (Palmer et al., 2018). A lack of aphasia education and training for PWA, caregivers and other healthcare professionals was reported in the Hong Kong survey (Kong & Tse, 2018); and there was a lack of aphasia information for friends in Australia (Rose et al., 2014). A lack of access to group and intensive therapy, limited follow‐up, and a general lack of community support services particularly in rural areas was also reported in the Australian survey (Rose et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In Hong Kong, speechlanguage pathologists in community settings may receive referrals from any source to provide assessment and treatment to patients though speech-language pathologists in hospitals may only receive referrals from doctors. According to the results of a recent clinician survey study, the intensity and frequency of current speech and language pathology services in Hong Kong for individuals with acquired neurogenic communication disorders fell short of expectations and most "best practice" recommendations set in developed countries [8].…”
mentioning
confidence: 98%